Дата моей смерти: роман / М. Юденич - Юденич Марина (АСТ, 2003)
Экземпляры: Ф. 13 (20200131) / Инвентарный номер: 47592 / Цена: 70.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Ю 16 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44